Sifat fisik dan mekanik kayu randu (Ceiba pentandra L. Gaerner) terdensifikasi dari hutan rakyat [Physical and mechanical properties of densified randu wood (Ceiba pentandra L. Gaerner) from community forest] - Galit Gatut Prakosa; Tatag Muttaqin; Rithya Suhestin (Jurnal Riset Industri Hasil Hutan, 2020)
Kapok wood has high potential availability of wood. Although, the weakness is its low quality. However, kapok wood quality can be improved by compaction technology. This research aims to improve the physical and mechanical properties of wood with wood compaction technology, and to determine the effect of variations in the horizontal position of trees and the length of steaming on the mechanical properties of compacted wood. The method used was compaction method with steaming treatment. The study used three types of wood method variations, namely terrace wood, transition wood and sapwood and four types of treatment with steaming duration of 30 minutes, 60 minutes, 90 minutes and without steaming. Wood testing on the physical properties of wood was guided by JIS Z 2102 (1957) and JIS Z 2103 (1957), while the mechanical properties of wood testing was guided by JIS Z 2113 (1963). Research showed that compaction on stretched wood with a target thickness of upto 2 cm improved the physical and mechanical properties of compacted wood. Steaming treatment prior to pressing for 90 minutes was effective in improving the mechanical properties of wood. The mechanical properties values improved by the increasing time of the steaming time before pressing the wood. The variation of wood position/parts affect the enhancement of the mechanical properties of wood in the parallel compressive strength test.